Topic prominence in Chinese EFL learners’ interlanguage - Li, Shaopeng; Yang, Lianrui (Studies in Second Language Learning and Teaching, 2014)
The present study aims to investigate the general characteristics of topicprominent typological interlanguage development of Chinese learners of English in terms of acquiring subject-prominent English structures from a discourse perspective. Topic structures mainly appear in Chinese discourse in the form of topic chains (Wang, 2002; 2004). The research target are the topic chain, which is the main topic-prominent structure in Chinese discourse, and zero anaphora, which is the most common topic anaphora in the topic chain. Two important findings emerged from the present study. First, the characteristics of Chinese topic chains are transferrable to the interlanguage of Chinese EFL learners, thus resulting in overgeneralization of the zero anaphora. Second, the interlanguage discourse of Chinese EFL learners reflects a change of the second language acquisition process from topic-prominence to subject-prominence, thus lending support to the discourse transfer hypothesis.